Preparation of curcumin submicron particles by supercritical antisolvent method with external adjustable annular gap nozzle - Yechen Wang; Zirui Li; Sun Fayu; Fei Li; Weiqiang Wang (Scientific Reports)
Abstract The supercritical antisolvent (SAS) method can effectively improve the bioavailability of poorly water-soluble drugs. However, the current supercritical equipment and processes were not fully developed, making industrialization difficult to achieve. Therefore, an externally adjustable annular gap nozzle and its supporting equipment were designed. Curcumin was used as a model drug, ethanol as the solvent, and supercritical carbon dioxide (SC-CO2) as the antisolvent. Building on single-factor experiments, a Box-Behnken Design-Response Surface Methodology (BBD-RSM) was employed to systematically investigate the effects of four process parameters—crystallizer pressure (12–16 MPa), crystallizer temperature (313–323 K), solution concentration (1–2 mg/mL), and CO2/solution flow rate ratio (133–173 g/g)—on the morphology and particle size of curcumin particles. Using scanning electron microscopy (SEM) and dynamic light scattering (DLS) analyses, morphologies and mean diameter ranges were examined. To look into how the SAS process affects TML’s chemical and physical characteristics, X-ray diffraction analysis (XRD) and Fourier-transform infrared spectroscopy (FT-IR) were further performed. Experimental results show that, flow ratio of CO2/solution had the greatest effect of particle size, followed by crystallizer temperature and solution concentration, while crystallizer pressure had the least influence. The optimum process conditions are operational conditions were set with a crystallizer pressure of 15 MPa, crystallizer temperature of 320 K, solution concentration of 1.2 mg/mL, and flow ratio of CO2/solution of 134 g/g, resulting in curcumin submicron particles with an average particle size of 808 nm being obtained. This study demonstrated the feasibility of an externally adjustable annular gap nozzle and its associated equipment in the SAS process, showcasing significant potential for reducing particles size and enhancing the bioavailability of poorly water-soluble drugs.